2015
DOI: 10.1166/jbn.2015.1973
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Poly(L-Lactic Acid) Aligned Nanofibers on PC12 Differentiation

Abstract: The aim of this study was to unveil the mechanism by which aligned nanofibers influence neuronal differentiation. PC12 cells were seeded on three different poly(L-lactic acid) (PLLA) substrates (PLLA films (control), electrospun PLLA random nanofibers (RF) and electrospun PLLA aligned nanofibers (AF)). Subsequently, cellular experiments, cDNA microarrays and molecular biological approaches were employed to investigate the impacts of the different PLLA substrates on PC12 cell differentiation. Scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 0 publications
3
36
0
Order By: Relevance
“…So, aligned nanofibers are one of the important surfaces as they provide aligned topography that the best suit to axonal guidance . Also, many studies have mentioned that aligned nanofibers could promote neural stem cell differentiation, especially when coupled with nerve growth factor (NGF) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, aligned nanofibers are one of the important surfaces as they provide aligned topography that the best suit to axonal guidance . Also, many studies have mentioned that aligned nanofibers could promote neural stem cell differentiation, especially when coupled with nerve growth factor (NGF) …”
Section: Introductionmentioning
confidence: 99%
“…7 Also, many studies have mentioned that aligned nanofibers could promote neural stem cell differentiation, especially when coupled with nerve growth factor (NGF). [8][9][10][11] As it is known neurons are electrically active cells which their electrical activity originates from the opening and closing of specific ion-channel proteins in the plasma membrane and help them to conduct, transmit, and receive electric signals. So using conductive electroactive biomaterials with the ability to support this phenomenon is very important in nerve tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…fiber diameter, porosity, and the newer area of micro-to macro-scale patterns, electrospun materials exhibit various other fascinating morphologies, such as helical, ribbonlike, beads-on-a-string, multi-channel tubular, porous honeycomb, nanoporous, nanopillared, core-shell and hollow structures, many of which are also observed in nature. [14][15][16] Control over the surface properties of ultrathin films, such as wettability and adsorption behavior, are important in a wide variety of applications, including surface selfcleaning, antiadhesives, biosensing, and separations. 17 The Layer-by-Layer (LbL) self-assembly technique presents a great advantage over many other coating techniques in that it is possible to control and finely tune the thickness and structure of the coating on a nanometer scale, simply by adjusting factors such as the ionic strength, pH and the number of dipping cycles.…”
Section: Introductionmentioning
confidence: 99%
“…19 Our previous study found that aligned nanofibers could promote PC12 cell differentiation via p-ERK1/2 mediated signal pathway. 20 Some other studies also showed that integrins can trigger p-ERK1/2 to further affect more gene transcription. 21 We implied that integrins may also fulfill their functions by inducing the expression of p-ERK1/2 in the aligned PLLA nanofibers-SH-SY5Y cells interaction.…”
Section: Effects Of Aligned Plla Nanofibers On Thementioning
confidence: 96%